A Hybrid Wireless Sensor Network Protocol for Time-Sensitive Emergency Operations - Anguraj, Dinesh Kumar (IRO Journal on Sustainable Wireless Systems, 2022)
Wireless sensor networks consists of nodes that are connected via wireless links and collaborate to self-organize into a network without utilizing any centralized infrastructure. Sensor networks encompass a wide range of paradigms and from that this research study focuses on the mobile networks, which recently significant potential for public/commercial environments and emergency disaster management services. Despite the hype, the wireless mobile networks are also experiencing the challenges such as communication failure, power consumption and network lifetime challenges. This paper presents a hybrid K-Means and Logistic Regression (LR) based algorithm to build a time sensitive multi hop communication to identify the shortest path to the base station and establish a flawless long distance communication. The proposed model metrics are defined to handle an emergency search and rescue operations in India. The NS2 simulator has been used to simulate the efficiency of the proposed model. The following metrics are utilized to analyse the performance: energy consumption, packet delivery ratio (PDR) and network lifetime.
Keywords: Mobile Adhoc Networks (MANET); emergency operations; Mo-LEACH; time-sensitive model